Rapamycin Added to Diet in Late Mid-Life Delays Age-Related Hearing Loss in UMHET4 Mice - Altschuler, Richard A.; Kabara, Lisa; Martin, Catherine; Kanicki, Ariane; Stewart, Courtney E.; Kohrman, David C.; Dolan, David F. (Frontiers in Cellular Neuroscience, 2021)
Our previous study demonstrated rapamycin added to diet at 4 months of age had significantly less age-related outer hair cell loss in the basal half of the cochlea at 22 months of age compared to mice without rapamycin. The present study tested adding rapamycin to diet later in life, at 14 months of age, and added a longitudinal assessment of auditory brain stem response (ABR). The present study used UMHET4 mice, a 4 way cross in which all grandparental strains lack the Cdh23753A allele that predisposes to early onset, progressive hearing loss. UMHET4 mice typically have normal hearing until 16-17 months, then exhibit threshold shifts at low frequencies / apical cochlea and later in more basal high frequency regions. ABR thresholds at 4, 12, 24 and 48 kHz were assessed at 12, 18, and 24 months of age and compared to baseline ABR thresholds acquired at 5 months of age to determine threshold shifts (TS). There was no TS at 12 months of age at any frequency tested. At 18 months of age mice with rapamycin added to diet at 14 months had a significantly lower mean TS at 4 and 12 kHz compared to mice on control diet with no significant difference at 24 and 48 kHz. At 24 months of age, the mean 4 kHz TS in rapamycin diet group was no longer significantly lower than the control diet group, while the 12 kHz mean remained significantly lower. Mean TS at 24 and 48 kHz in the rapamycin diet group became significantly lower than in the control diet group at 24 months. Hair cell counts at 24 months showed large loss in the apical half of most rapamycin and control diet mice cochleae with no significant difference between groups. There was only mild outer hair cell loss in the basal half of rapamycin and control diet mice cochleae with no significant difference between groups. The results show that a later life addition of rapamycin can decrease age-related hearing loss in the mouse model, however, it also suggests that this decrease is a delay/deceleration rather than a complete prevention.